Pewarisan Sifat Resistensi terhadap Deltametrin pada Plutella xylostella - Wahyu Listyaningrum; Y. Andi Trisyono; Aziz Purwantoro (Jurnal Perlindungan Tanaman Indonesia, 2003)
A field population of Plutella xylostella (Lepidoptera: Plutellidae) in Central Java has been reported to become resistant to a pyretroid synthetic deltamethrin. The objective of this research was to study the genetics of resistance in that population. The resistant population wascontinously sprayed with deltamethrin in the laboratory to increase the resistant level. The resistant population used in this study was 51 more resistant to deltamethrin than was the susceptible population. Bioassays using F1 obtaining from the reciprocal mating between the susceptible and resistant parents showed that the resistance to deltamethrin in P. xylostella was inherited recessively and the maternal effects were observed. The degree of dominance (D) was -0.8 when resistant female was mated with the susceptible male and the D value was -0.3 when the susceptible female was mated with the resistant male. Using the monogenic model it was proved that the resistance was controlled by single gen. The implementation of these findings for the development of resistance management program will be discussed.